Early life growth of the Bali sardine (Sardinella lemuru) in the Northern Zamboanga upwelling system inferred from otolith microstructure - Bagarinao, Alexandra A. (University of the Philippines Visayas, 2018)
Understanding the factors that strongly influence early life growth and subsequent recruitment is vital to predicting favorable and unfavorable conditions for population persistence and resilience. Otoliths were used to examine early life growth patterns of early stages of Sardinellalemuru, in NorthenZamboanga Peninsula (NZP) over a 2-year period (2011-2012 and 2012-13 spawning seasons). Back-calculated size at hatch of S. lemuru in this study corresponded well with the reported size (diameter) of hydrated eggs released during spawning (0.156-0.539mm). Newly hatched individuals are small and falls within the lower range of reported size at hatch of other clupeiforms. Mean growth rate of individuals hatched in 2011-12 (0.78 mm day-1) was significantly lower compared to individuals hatched in 2012-13 (0.90 mm day-1). Even with significant differences observed between years, trends in growth trajectories appeared to be consistent, with individuals hatched in the middle of the season (January 2012 and 2013) displaying faster larval growth rates than those hatched early and late in the season. The results show that growth and survival was strongly correlated toenvironmental conditions, such that a combination of cooler temperatures and elevated food levels in the NZP resulted to higher growth rates. Moreover, exposure to such conditions mayhave allowed for compensatory growth to occur in 2012-2013 year-class which were hatched significantly smaller than 2011-2012 year class. Because spawning is generally timed with highlevels of productivity (e.g. peak chlorophyll concentrations) it may be possible to develop indicators of "good" or bad of local sardine fishery with enhanced understanding of their early life history.